Respostas
respondido por:
6
Dados:
y = 3x + 5 ⇒ dy/dx = 3
dy/dt = - 1
dx/dt = dy/dt . dx/dy
dx/dt = (- 1) . 1/(dy/dx)
Porém dy/dx = 3
dx/dt = (- 1) . 1/3
dx/dt = - 1/3
Como dx/dt é uma constante e independe de x, para qualquer valor de x o resultado é = - 1/3.
y = 3x + 5 ⇒ dy/dx = 3
dy/dt = - 1
dx/dt = dy/dt . dx/dy
dx/dt = (- 1) . 1/(dy/dx)
Porém dy/dx = 3
dx/dt = (- 1) . 1/3
dx/dt = - 1/3
Como dx/dt é uma constante e independe de x, para qualquer valor de x o resultado é = - 1/3.
respondido por:
0
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás